Understanding fetal alcohol spectrum disorder : a guide to FASD for parents, carers and professionals - Catterick, Maria (JKP essentials., 2014)
This is the essential guide to FASD - the most common non-genetic learning disability, which is caused by alcohol consumption during pregnancy. It explains how FASD affects individuals at different stages of their lives, how you can identify it, and gives advice on how to support children, young people and adults with FASD.